(untitled) (Applied Biological Research, 2025)
Climate variability plays a crucial role in regulating the phenological patterns of plants and the developmental dynamics of associated insects. This study examined the phenology of willow (Salix alba) and the developmental stages of the gypsy moth (Lymantria obfuscata) over two consecutive years (2022–2023) using Julian dates and accumulated degree days (DD). Significant inter-annual variations were observed in both plant and insect development. In 2022, vegetative bud burst occurred earlier (Julian day 53, 0.55 DD) than in 2023 (Julian day 60, 3.86 DD), with similar delays observed in flowering and late-season events. Increased DD requirements in 2023 suggest climatic influences on phenological timing.Gypsy moth development also showed temporal shifts. In 2022, key stages such as egg hatching and adult emergence occurred earlier and at lower DD thresholds compared to 2023. Adult emergence was recorded at Julian day 158 (945.30 DD) in 2022 and at day 165 (492.22 DD) in 2023, indicating altered developmental dynamics. Population peaks differed between years, with a mid-June peak in 2022 (40 individuals, 608.65 DD) and a delayed, smaller peak in 2023 (35 individuals, 593.88 DD). These findings highlight the influence of temperature on plant–insect synchrony and demonstrate the usefulness of degree-day models for predicting phenological responses under changing environmental conditions.